The quality of life in Sustainable Urban Mobility Planning. The case study of the Polish city of Piotrków Trybunalski - Wołek, Marcin; Hebel, Katarzyna (Jakość życia w planowaniu zrównoważonej mobilności miejskiej. Studium przypadku polskiego miasta Piotrkowa Trybunalskiego, 2019)
The quality of life is nowadays one of the leading socio-economic and political topics. On an urban level its importance is growing as the megatrend of urbanization is reconstructing the global map of megacities. By 2050, two-thirds of the global population will live in cities. Therefore quality of life, although difficult for objective measurement, is one of the most important issues in sustainable urban planning for cities. An important element influencing quality of life is ‘motorization’ with its positive and negative impacts. Using the example of Piotrków Trybunalski, a medium-sized Polish city that has already adopted the Sustainable Urban Mobility Plan, the evaluation of the quality of life is presented. Data collected in October 2019 was used. The residents were divided into segments based on intensity of their car usage. Particular segments are differentiated according to the modal split and daily mobility index of citizens. The assessment of the quality of life in Piotrków Trybunalski is quite similar for citizens with different access to car usage, although it has a tremendous impact on their modal split
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 129-143